Examination of inter-rater and intra-rater reliability during retentive force measurement of different clasps using the developed small-sized retentive force measurement device - Hitoshi Akiyama; Maiko Sakamoto; Ryoichi Akama; Jun Takei (BMC Oral Health, 2020)
Abstract Background The design process of a removable partial denture (RPD) consists of rests, major connectors, minor connectors, denture base, and retainer. The abutment tooth contour determines the location of the retention portion of the clasp at the retention areas. The load capacity of the clasp depends on various factors such as type, the position of a clasp, tooth position, clasp length, and pullout location. As a general rule, the amount of retention required to dislodge the RPD from the supporting structure should always be the minimum necessary to resist reasonable dislodging forces. Excessive force from the clasps may cause many problems. Although there are many reports on the retentive force of cast clasps using large devices, it has not been possible to measure it using simple devices until now. Method The purpose of the present study is to develop a small-sized retentive force measurement device that can easily measure the retentive force of a clasp used for an RPD. It is to examine inter-rater and intra-rater reliability. A small-sized retentive force measurement device that can be easily measured in the laboratory has been developed. Using commercially available hard plaster cast, a skilled dental technician has made 10 types of cast clasps used in clinical practice using conventional techniques. Three assessors measured the retentive force of 10 types of cast clasps. To confirm the reliability, the intra-class correlation coefficients ICC (1,1) and ICC (1,3) of the 3 assessors were calculated, and the reliability within the assessor was examined. The inter-class correlation coefficients ICC (3,1) and ICC (3,3) were calculated, and the reliability of the assessors was examined. Result The intra-class correlation coefficients of 3 assessors are as follows: assessor 1 has ICC (1,1) = 0.971, ICC (1,3) = 0.990, assessor 2 has ICC (1,1) = 0.967, ICC (1,3) = 0.989, assessor 3 has ICC (1,1) = 0.962, ICC (1,3) = 0.987. The inter-class correlation coefficients of 3 assessors are as follows: ICC (3,1) = 0.993, ICC (3,3) = 0.998. From the evaluation standard of the intraclass correlation coefficients of reliability value by ICC, it was evaluated as almost perfect and high reproducibility was confirmed. Conclusion The developed small-sized retentive force measurement device has reproducibility within and between the assessors.